Tomoelastography paired with T2∗ magnetic resonance imaging detects lupus nephritis with normal renal function - Garcia, Stephan Rodrigo Marticorena; Grossmann, Markus; Bruns, Anne; Duerr, Michael; Tzschaetzsch, Heiko; Hamm, Bernd; Braun, Juergen; Sack, Ingolf; Guo, Jing (Investigative Radiology, 2019)
Objectives The aim of this study was to test multiparametric magnetic resonance imaging including blood oxygen level-dependent (BOLD) imaging by T2∗ mapping, magnetic resonance elastography (MRE) by tomoelastography, and diffusion-weighted imaging (DWI) for detecting nephropathy in patients with lupus nephritis (LN). Methods Forty-one subjects (25 patients with LN and 16 age- and sex-matched healthy volunteers; LN: mean age, 47.3 ± 14.8 years; 22 female subjects; volunteers: mean age, 43.9 ± 11.6 years; 13 female subjects) were prospectively enrolled. The LN group was further divided into subgroups with normal (LN-nRF, GFR > 90 mL/min per 1.73 m 2 ) and compromised renal function (LN-cRF, GFR < 90 mL/min per 1.73 m 2 ). All subjects were examined by multifrequency MRE, BOLD imaging, and DWI, yielding shear wave speed (SWS; in meter per second), T2∗ relaxation times (in millisecond), and apparent diffusion coefficient (ADC; in millimeter square per second), respectively. Renal subregional analysis was performed for the medulla (ME), inner cortex (CoI), and outer cortex (CoO). Imaging markers were correlated to clinical parameters such as GFR and protein-to-urine creatinine ratio. Cutoffs and area under the receiver operating curve (AUROC) were computed to test diagnostic performances. Results Compared with CoI and CoO, LN-nRF predominantly affects ME tissue (SWS: -7%, P < 0.01; T2∗: +9%, P < 0.05; ADC: -5%, P = 0.27). Detection of LN-nRF was better with MRE compared with BOLD imaging and DWI (AUROC = 0.81, 0.76, not significant), whereas pairing MRE with T2∗ further increased diagnostic power (AUROC = 0.91). Disease progression was associated with reduction of SWS also in CoI (LN-nRF, 3.04 ± 0.38 m/s; LN-cRF, 2.60 ± 0.26 m/s; p = 0.013), allowing distinction of LN-nRF from LN-cRF (AUROC = 0.83). Diffusion-weighted imaging was only sensitive to LN-cRF in ME tissue (ADC, -12%; P < 0.05). Conclusions Lupus nephritis with normal renal function first arises in MRE and BOLD images within ME tissue, progressing to CoI tissue once renal function becomes impaired and diffusion of tissue water changes.
CRIS-Team Scopus Importer:2022-08-03
Keywords: blood oxygen level-dependent; diffusion-weighted imaging; elastography; lupus nephritis; magnetic resonance elastography